Development and Initial Validation of a Brief Measure of TikTok Addiction in a Multi-Country Sample - Feten Fekih-Romdhane; Amira Mohammed Ali; Hanaa Ahmed Mohamed Shuwiekh; Mai Helmy; Abdallah Y Naser; Kamel Jebreen; Sami El Khatib; Mirna Fawaz; Tasnim Swaitti; Eqbal Radwan; Inad Nawajah; Diana Malaeb; et al. (Journal of Primary Care & Community Health)
Background: The dramatic increase in TikTok use over the past few years has generated a major challenge globally. Providing researchers with a valid, reliable, yet brief measure may stimulate large-scale epidemiological research that can help to clarify the mechanisms involved in susceptibility to TikTok addiction and guide the development of prevention strategies. The objective of our study was to design and validate a brief measure that we labelled the TikTok Addiction Test (TAT) using a multi-country sample, with a specific focus on measuring the 6 core features of addiction through 1 item each. Method: A multi-country survey with a cross-sectional design was conducted in February of 2025 among general population adults (N = 3362) from five Arab countries: Egypt, Jordan, Lebanon, Oman, and Palestine. Results: A single-factor solution was obtained in the Exploratory Factor Analysis and corroborated in the Confirmatory Factor Analysis, indicating an adequate goodness-of-fit indices, with all 6 items satisfactorily loading on the same latent variable. In addition, the internal consistency reliability indicators were excellent for the entire measure, with Cronbach’s alpha and McDonald’s omega values of 0.91. We found invariance in factor structure, factor loadings, and intercepts between sexes and for country groups. A total of 207 (6.2%) participants were identified as TikTok addicts. Females exhibited significantly higher mean TAT scores than males. Palestinian and Lebanese participants reported the highest TikTok addiction scores, followed by Egyptians, Jordanians, and Omani. Finally, significant positive associations were observed between TAT scores and smartphone addiction, depression, anxiety, and loneliness, supporting the concurrent validity of the scale. Conclusion: Results suggest that the TAT is a simple and useful instrument for measuring TikTok addiction of general population adults with only 6 items and 1 factor. As a brief self-report measure, the TAT can be highly valuable in time- and resource-pressured real-life settings, and offers a foundation for future research in this area.